The Correlation Between Disease Activity Assessed by DAS28-ESR and Quality of Life Assessed by SF-36 in Rheumatoid Arthritis Patients - Putri Vidyaniati; Rachmat Gunadi Wachjudi; Anna Tjandrawati; Laniyati Hamijoyo (Indonesian Rheumatology Association, 2018)
Background Rheumatoid arthritis is the most prevalent form of inflammatory arthritis. One of the key components for its multidimensional outcome is the disease activity, measured by DAS28-ESR. The physical, emotional, and social aspects of RA contribute to the quality of life, and SF-36 questionnaire can be used to measure it. This study aims to ascertain the correlation between the disease activity (DAS28-ESR) and the quality of life (SF-36) in RA patients. Method This study was an analytical, descriptive study with a cross sectional design that took primary data from RA patients undergoing treatment in Rheumatology Clinic of Hasan Sadikin Hospital from February to April 2015. The patientâ€™s data included sex, age, marital status, employment status, educational level, serostatus (RF and Anti-MCV), duration of diagnosis, total number of medications, total number of DMARD, DAS28-ESR scores, and SF-36 scores. The data was analysed with the Shapiro-Wilk normality test, followed by the Rank-Spearman correlation analysis. Result There were 42 subjects, with an average age of 41 Â± 12. The ratio between females and males was 20:1, and the majority of subjects (73,8%) had a positive serostatus (RF and/or anti-MCV). The score median of DAS28-ESR was 4,3, with the score median for SF-36 PCS being 39,8 and the score median for SF-36 MCS being 48,2. Based on the the Rank-Spearman analysis (CI of 95%), there was a correlation between DAS28-ESR score and SF-36 PCS score, with the correlation coefficient (r) of -0,577 (p < 0,001), and there was also a correlation between DAS28-ESR score and SF-36 MCS score with r of -0,368 (p = 0,008). Conclusion There was a strong negative correlation between disease activity and physical component of quality of life, and a moderate negative correlation between disease activity and mental component of quality of life, and the two correlations were statistically significant.